2009
DOI: 10.1016/j.cryobiol.2009.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Interactions among pre-cooling, cryoprotectant, cooling, and thawing for sperm cryopreservation in rhesus monkeys

Abstract: The present study evaluated the interactions among pre-cooling, cryoprotectant, cooling, and thawing for rhesus monkey sperm using a four-way factorial design. Specifically, pre-cooling and thawing were evaluated for two conditions: slow vs. fast. Cooling was evaluated at four rates of 5, 29, 200, and 400 °C/min. The types of cryoprotectant involved combinations of egg yolk and glycerol, egg yolk and ethylene glycol, and egg yolk alone without permeable cryoprotectants or buffer alone with glycerol but without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 37 publications
(40 reference statements)
1
17
1
Order By: Relevance
“…A previous study on rhesus sperm cryopreservation with EG showed that 2 and 4% EG (corresponding to 0.28 and 0.56 M, respectively) were optimal for preserving rhesus sperm motility [2]. However, in our study, a low level (0.175 and 0.35 M) of EG was insufficient to preserve rhesus sperm motility compared with 0.7 M EG.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…A previous study on rhesus sperm cryopreservation with EG showed that 2 and 4% EG (corresponding to 0.28 and 0.56 M, respectively) were optimal for preserving rhesus sperm motility [2]. However, in our study, a low level (0.175 and 0.35 M) of EG was insufficient to preserve rhesus sperm motility compared with 0.7 M EG.…”
Section: Discussioncontrasting
confidence: 51%
“…The optimal Gly concentration for rhesus sperm cryopreservation is 5% (0.7 M) [20], which is consistent with the results for cynomolgus macaque sperm cryopreservation [19]. In addition to Gly, other types of penetrating CPAs, including dimethyl sulfoxide (DMSO), propylene glycol (PG) and ethylene glycol (EG), have been applied for cryopreservation of nonhuman primate sperm [2,3,7,11,20]. However, study of the fundamental cryobiology of rhesus macaque sperm indicated that EG is the most appropriate CPA for cryopreservation of rhesus macaque sperm due to its higher permeability coefficient compared with Gly, DMSO and PG [1].…”
supporting
confidence: 65%
See 2 more Smart Citations
“…It has been alternatively argued that slow warming may be beneficial to allow time for osmotic re-equilibration processes to take place [25] when the highly shrunken cells start to encounter more liquid water as the ice matrix melts at high subzero temperatures. In some experiments on particular cell types, the impact of slow versus fast warming was either not significant or was related to the particular CPA used [44]. This raises another potential warming factor -exposure of the cells to toxic high CPA concentrations at high subzero temperatures during slow warming.…”
Section: Considerations For Warmingmentioning
confidence: 99%